Investigation of protein arginine methyltransferase bisubstrate inhibitors - Al-noori, Alaa (2020)
Protein arginine methylation is a significant post-translational modification which is catalysed by protein arginine methyltransferases (PRMTs). PRMTs catalyse the transfer of methyl group from the cofactor S-adenosyl-L-methionine (SAM) to arginine residues which are present in proteins. Dysregulation of these enzymes has been associated with cellular diseases such as prostate cancers, cardiovascular disease, and spinal muscular atrophy.